Antibacterial carbazole alkaloids from Clausena harmandiana twigs - Wisanu Maneerat (2018)
Three new carbazole alkaloids, harmandianamines A-C (1-3), together with fifteen known compounds (4-18) were isolated from the twigs of Clausena harmandiana. The structures were elucidated by spectroscopic methods, including UV, IR, NMR, and MS. The antibacterial activity against Escherichia coli TISTR 780, Salmonella typhimurium TISTR 292, Staphylococcus aureus TISTR 1466 and methicillin-resistant S. aureus (MRSA) SK1 of some isolated compounds was also evaluated. Compound 6 exhibited significant antibacterial activity against MRSA SK1 with an MIC value of 0.25 μg/mL which higher than that of standard drug, vancomycin (MIC value = 1 μg/mL) whereas compounds 14 and 5 showed strong activity with MIC values of 4 and 8 μg/mL, respectively. Only compound 14 showed strong antibacterial activity against S. aureus TISTR 1466 with an MIC value of 4 μg/mL. © 2012 Elsevier B.V. All rights reserved.